The use of ultrasound to evaluate sacrococcygeal epidural injections in cats - Credie, Leonardo [UNESP]; Luna, Stelio [UNESP] (Canadian Vet Med Assoc, 2018)
Ultrasonography of the lumbosacral and sacrococcygeal spine is described in cats to confirm effective distribution of local anesthetics injected in the sacrococcygeal epidural space. Ultrasound was used to identify the structures of the spinal canal, local anesthetic flow, and to measure the distances between skin and ligamentum flavum.